Green synthesized materials for sensor, actuator, energy storage and energy generation: a review. Issue 1 (2nd January 2020) - Ponnamma, Deepalekshmi; Parangusan, Hemalatha; Deshmukh, Kalim; Kar, Pradip; Muzaffar, Aqib; Pasha, S. K. Kadheer; Ahamed, M. Basheer; Al-Maadeed, Mariam Al Ali
ABSTRACT: Green synthesis methods have attracted enormous research interest as replacements for dangerous chemicals due to their abundance and eco-friendliness. The remarkable properties of green synthesized materials include environmental friendliness, high abundance, antimicrobial, antioxidant and biodegradability. The integration of green synthesized materials in electronic devices not only enhances the economic benefit of natural waste resources but also conserves our environment. This review article is dealing with the current research efforts in green synthesized materials trends, challenges and their potential applications in sensors, actuators, energy storage and energy generation.